2010
DOI: 10.1183/09031936.00049410
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammatory bowel disease risk loci with sarcoidosis, and its acute and chronic subphenotypes

Abstract: Sarcoidosis is a complex granulomatous inflammatory disorder that shares several clinical and pathogenic features with inflammatory bowel disease (IBD). Postulating a common genetic basis of inflammatory diseases, we tested 106 single-nucleotide polymorphisms (SNPs) that are known or have been suggested to be associated with IBD for a potential association with sarcoidosis and its acute and chronic subphenotypes.We genotyped 1,996 German sarcoidosis patients, comprising 648 acutely and 1,161 chronically affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 59 publications
0
48
0
Order By: Relevance
“…Thus, in susceptible individuals, inanimate remnants of bacteria or remote infection may be capable of inducing sustained sarcoid-like inflammation (51,52). The nature of these disease susceptibilities may be queried in genome-wide association studies, which have identified a number of gene variants associated with sarcoidosis and other granulomatous disorders (53)(54)(55). Another approach is the identification of molecular signatures by systems biology approaches using peripheral blood cells or lung tissue.…”
Section: Other Dplds Sarcoidosismentioning
confidence: 99%
“…Thus, in susceptible individuals, inanimate remnants of bacteria or remote infection may be capable of inducing sustained sarcoid-like inflammation (51,52). The nature of these disease susceptibilities may be queried in genome-wide association studies, which have identified a number of gene variants associated with sarcoidosis and other granulomatous disorders (53)(54)(55). Another approach is the identification of molecular signatures by systems biology approaches using peripheral blood cells or lung tissue.…”
Section: Other Dplds Sarcoidosismentioning
confidence: 99%
“…Polymorphisms in rs11209026 can affect serum IL-17A levels in rheumatoid arthritis patients [116]. In a German cohort, rs11209026A was protective against chronic sarcoidosis [117].…”
Section: Il-23mentioning
confidence: 99%
“…They both share multi-organ manifestations (joints, eye, skin). Sarcoidosis and IBD seem to share a genetic overlap regarding cytoplasmic nucleotide oligomerization domains 1 and 2 and certain polymorphisms in chromosomes 1 (loci IL-23R and 1q.24.3) and 15 (locus HERC2) [63] . IBD, as discussed earlier in this article, may exhibit granulomatous lung disease, mainly bronchiolitis.…”
Section: Concomitant Diseases Involving the Airwaysmentioning
confidence: 99%